Modelling long-term electricity contracts at EEX - Robert Flasza; Milan Rippel; Jan Šolc (Charles University in Prague, Institute of Economic Studies (IES), 2011)
The main aim of this paper is to develop and calibrate an econometric model for modelling prices of long term electricity futures contracts. The calibration of our model is performed on data from EEX AG allowing us to capture the specific features of German electricity market. The data sample contains several structural breaks which have to be taken into account for modelling. We model the data with an ARIMAX model which reveals high correlation between the price of electricity futures contracts (namely Phelix Base Fututes with next year's delivery) and prices of long-term futures contracts of fuels (namely coal, natural gas and crude oil). Besides this, also a share price index of representative electricity companies traded on Xetra, spread between 10Y and 1Y German bonds and exchange rate between EUR and USD appeared to have significant explanatory power over these futures contracts on EEX.
Keywords: C32; C53; G13; O13; 330; electricity futures; EEX; ARIMAX; emission allowances